Q. 184.6( 15 Votes )

Solve for x:
<

Answer :

We have,





(2x2 + 4) (x – 2) = (2x – 11) (x2 + x – 2)


2x3 + 4x – 4x2 – 8 = 2x3 – 11x2 + 2x2 – 11x – 4x + 22


5x2 + 19x = 30


5x2 + 19x – 30 = 0


5x2 + 25x – 6x – 30 = 0


(x + 5) (5x – 6) = 0


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses